1985
DOI: 10.1067/mva.1985.avs0020214
|View full text |Cite
|
Sign up to set email alerts
|

Carotid endarterectomy in the stroke patient: Computerized axial tomography to determine timing

Abstract: Historically, patients with mild to moderate neurologic deficits lasting longer than 24 hours were believed to have sustained a completed stroke. They were followed up for 4 to 6 weeks and cerebral angiography was performed if indicated. CT scanning has identified a subset of these patients who have sustained a reversible ischemic neurologic deficit (RIND) rather than a completed stroke. The timing for angiography and surgery for this group has not been established. In an earlier study we found that 21% (4 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 0 publications
0
19
0
3
Order By: Relevance
“…11 Sacco et al 12 reported a 14% recurrent stroke rate within 2 years in 1273 patients with acute cerebral infarction, 30% of which occurred in the first 30 days. Dosick et al 10 observed a 9.8% recurrence of neurologic events in 74 patients within 4 to 6 weeks after an ischemic stroke. In the ECST trial 71 patients randomized to medical care suffered an ipsilateral ischemic stroke, 24% of which were observed within 4 months of randomization.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…11 Sacco et al 12 reported a 14% recurrent stroke rate within 2 years in 1273 patients with acute cerebral infarction, 30% of which occurred in the first 30 days. Dosick et al 10 observed a 9.8% recurrence of neurologic events in 74 patients within 4 to 6 weeks after an ischemic stroke. In the ECST trial 71 patients randomized to medical care suffered an ipsilateral ischemic stroke, 24% of which were observed within 4 months of randomization.…”
Section: Discussionmentioning
confidence: 99%
“…22 Possibly patients with stroke and no ischemic lesions on CT are a favorable selection for early surgery. Dosick et al 10 reported one stroke (0.9%) and no death in 110 patients operated within 14 days of a nondisabling stroke who had negative CT scans on days 1 and 5.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations